An economic perspective on new guidelines on regional aid for 2014-2020 Die neuen Leitlinien für EU-Regionalbeihilfen 2014 bis 2020 aus ökonomischer Sicht - Paha, Johannes (Wirtschaftsdienst, 2013)
This article analyses the European Commission's Guidelines on Regional State Aid for 2014-2020 that were passed in late June 2013. The author argues that some elements of these guidelines are neither in line with economic theory nor with related guidelines and communications of the Commission. Before applying the guidelines, some rules, e.g. on market delineation and foreclosure, should be defined more clearly. © 2013 ZBW and Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-11-17

Antitrust Compliance: Managerial Incentives and Collusive Behavior - Paha, Johannes (Managerial and Decision Economics, 2017)
This article analyzes a manager's incentives to establish and sustain an illegal collusive agreement if her firm is subject to profit shocks, if her utility function is concave in profits (e.g., because of risk aversion), and if she incurs opportunity costs (e.g., by violating a social norm). The model supports the empirical observation that if collusion is to be established and sustained in a state with low profits, then this state must be quite persistent. It also indicates that compliance with antitrust laws can be ensured best by combining a zero tolerance policy with a strategy of forgiveness. Copyright © 2017 John Wiley & Sons, Ltd.
CRIS-Team Scopus Importer:2022-11-17

Carbon Pricing Influences Competition — and Benefits From It CO2-Bepreisung beeinflusst den Wettbewerb — und profitiert von ihm - Paha, Johannes (Wirtschaftsdienst, 2022)
This article studies the interaction effects between climate change policies, especially German and European emission trading schemes, and competition. It demonstrates why the effectiveness of those policies is diminished in markets characterized by market power, and how antitrust laws can improve this situation. Emissions trading may also reduce the competitiveness of German and European companies internationally. In response, there have been calls for its modification, which may, however, cause subsidy races and tax competition. State aid control as an element of European competition policy, world trade law and climate diplomacy counteract these effects.
CRIS-Team Scopus Importer:2022-11-17

Cartels as Defensive Devices: Evidence from Decisions of the European Commission 2001-2010 - Herold, Daniel; Paha, Johannes (Review of Law and Economics, 2018)
Why would an industry that was not colluding yesterday start colluding today? This article distills insights about cartel formation from 41 cases prosecuted by the European Commission between 2001 and 2010. The case studies examine the events occurring prior to the cartels' set-up. Cartel formation is affected by changes in prices, demand and customer conduct, capacity utilization, increased imports and entry by competitors, as well as events in the legal and regulatory environment of the firms. Yet, none of these factors serves as a good marker of cartel formation when being regarded in isolation. It rather needs to be analyzed how changes in these factors interact and whether they raise the intensity of competition. In this context, factors that are commonly deemed to destabilize cartels, like entry of new competitors or buyer power, are found to actually foster cartel formation.
CRIS-Team Scopus Importer:2022-11-17
Keywords: cartel formation; case study; collusion

Competition law compliance programmes: An interdisciplinary approach - Paha, Johannes (Springer International Publishing, 2016)
This book reviews and presents antitrust law compliance programmes from different angles. These programmes have been increasingly implemented and refined by firms over recent years, and various aspects of this topic have been researched. The contributions in this book extend beyond the treatment of legal issues and show how lawyers, economists, psychologists, and business scholars can help design antitrust law compliance programmes more effectively and run them more efficiently.
CRIS-Team Scopus Importer:2022-11-17

Customer choice patterns in passenger rail competition - Paha, Johannes; Rompf, Dirk; Warnecke, Christiane (Transportation Research Part A-Policy and Practice, 2013)
This study explores determinants of customer choice behaviour in passenger rail competition on two cross-border routes, Cologne-Brussels and Cologne-Amsterdam. It fills a gap in the literature on competition in commercial passenger rail by relying on newly collected stated preference data from about 700 on-train interviews. Our multinomial Logit estimations reveal two important effects that are closely connected to (psychological) switching costs. First, the customers on the route Cologne-Amsterdam, for whom competition is a purely hypothetical situation, value a competitive market structure lower than customers on the already competitive route Cologne-Brussels. Second, travellers show a status quo bias with a preference for the service provider on whose trains they were interviewed. This effect goes beyond the impact exercised by explanatory variables capturing the observable differences of the services and customers, including loyalty-enhancing effects like the possession of customer cards. Our results imply that entry into the commercial passenger rail market may be more difficult than often thought. Thus, the study contributes to explaining the low level of competition in these markets in Europe. © 2013 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Competition; Discrete choice; Multinomial Logit; Passenger; Rail; Transport

Empirical methods in the analysis of collusion - Paha, Johannes (Empirica, 2011)
Regression methods are commonly used in competition lawsuits for, e.g., determining overcharges in price-fixing cases. Technical evaluations of these methods' pros and cons are not necessarily intuitive. Appraisals that are based on case studies are descriptive but need not be universally valid. This paper opens up the black box called econometrics for competition cases. This is done by complementing theoretical arguments with estimation results. These results are obtained for data that is generated by a simulation-model of a collusive industry. Using such data leaves little room for debate about the quality of these methods because estimates of, e. g., overcharges can be compared to their true underlying values. This analysis provides arguments for demonstrating that thoroughly conducted econometric analyses yield better results than simple techniques such as before-and-after comparisons. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Collusion; Empirical methods; Industry simulation

IT Sector: Opportunities for the German-Nigerian Economic and Development Partnership IT-Sektor: Chancen für die deutsch-nigerianische Wirtschafts- und Entwicklungspartnerschaft - Paha, Johannes; Wolter, Lydia (Wirtschaftsdienst, 2021)
The emergence and growth of the largest African market for information and communication technology in Lagos, Nigeria, is based on agglomeration effects and the interaction between complementary success factors that have positive externalities. Necessary reforms that are supposed to be implemented through national measures to eliminate market failures as well as international measures in development policy require a market transition into the formal economy. However, this necessity runs the risk of destroying the successful interplay between the factors of success. This article illustrates the opportunities and risks for German-Nigerian economic and development cooperation.
CRIS-Team Scopus Importer:2022-11-17

List Price Collusion - Boshoff, Willem H.; Paha, Johannes (Journal of Industry, Competition and Trade, 2021)
Firms sometimes collude by agreeing on increases in list prices. Yet, the efficacy of such list price collusion is subject to discussion as colluding firms might, in principle, deviate secretly from the elevated prices by granting their customers discounts. This article reviews cases of list price collusion in the USA and Europe, and it presents a theory of harm suggesting that a combination of anchoring, orientation on reference points, and loss aversion may render list price collusion effective in raising transaction prices—even if firms set transaction prices in a non-coordinated fashion.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Anchoring; Antitrust; Cartel; Collusion; Discount; List price; Reference prices

Managing antitrust risks in the banking industry - Scheld, Denise; Paha, Johannes; Fandrey, Nicolas (European Competition Journal, 2016)
Ensuring compliance with competition laws has become increasingly important in the banking industry as the number of cases prosecuted and the fines imposed by competition authorities are on the rise. This article presents the costs and benefits of antitrust risk management, arguing that such risk management efforts are essential for ensuring banks’ survival and maximizing their value. The article sets out an approach to assessing the residual risk of non-compliance with antitrust laws and shows how antitrust risk management can be implemented efficiently in banks’ existing risk management structures using the Three Lines of Defence model and the COSO ERM framework.
CRIS-Team Scopus Importer:2022-11-17
Keywords: antitrust; banks; competition; compliance; risk management

Non-Controlling Minority Shareholdings and Collusion - De Haas, Samuel; Paha, Johannes (Review of Industrial Organization, 2021)
This article merges theoretical literature on non-controlling minority shareholdings (NCMS) in a coherent model to study the effects of NCMS on competition and collusion. The model encompasses both the case of a common owner holding shares of rival firms as well as the case of cross ownership among rivals. We find that by softening competition, NCMS weaken the sustainability of collusion under a greater variety of situations than was indicated by earlier literature. Such effects exist, in particular, in the presence of an effective competition authority.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Collusion; Common ownership; Cross ownership; Minority shareholdings

Optimization heuristics for determining internal rating grading scales - Lyra, M.; Paha, J.; Paterlini, Sandra; Winker, Peter (Computational Statistics & Data Analysis, 2010)
Basel II imposes regulatory capital on banks related to the default risk of their credit portfolio. Banks using an internal rating approach compute the regulatory capital from pooled probabilities of default. These pooled probabilities can be calculated by clustering credit borrowers into different buckets and computing the mean PD for each bucket. The clustering problem can become very complex when Basel II regulations and real-world constraints are taken into account. Search heuristics have already proven remarkable performance in tackling this problem. A Threshold Accepting algorithm is proposed, which exploits the inherent discrete nature of the clustering problem. This algorithm is found to outperform alternative methodologies already proposed in the literature, such as standard k-means and Differential Evolution. Besides considering several clustering objectives for a given number of buckets, we extend the analysis further by introducing new methods to determine the optimal number of buckets in which to cluster banks' clients. © 2009 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2022-11-17

Results of a survey in Germany, Austria, and Switzerland on how to prevent violations of competition laws - Götz, Georg; Herold, Daniel; Paha, Johannes (Springer International Publishing, 2016)
This report presents the results of a survey on competition law compliance in Germany, Austria, and Switzerland in which 86 large companies participated. The study shows that 80% of the firms have implemented measures to identify and mitigate the risks of violating competition laws. The majority of firms and measures concentrate on legal risks (e.g. insufficient awareness of the content and scope of competition laws), whereas risks related to changes in the economic environment (e.g. entry into the market, competition by imports, and more intense competition) are rarely addressed. Risk mitigation heavily relies on competition law training, even though these measures hardly seem sufficient. This is obvious from the fact that 71% of the firms whose employees had violated competition laws in the past had already trained these employees before the misconduct occurred. We conclude from our study that those measures should be improved that help to detect cartelisation risks at an early stage. Furthermore, sanctions imposed by the firms on the offenders of competition laws require a clearer design and more systematic communication.
CRIS-Team Scopus Importer:2022-11-17

Some Effects of EU Sugar Reforms on Development in Africa - Paha, Johannes; Sautter, Timon; Schumacher, Reinhard (Inter economics, 2021)
The sugar industry is a major provider of jobs and income for sugar-exporting countries in Africa. The lower sugar prices that were caused by the recent liberalisation of the EU sugar market may not only jeopardise economic development in those countries, but the reforms also create difficulties for sugar-importing countries in Africa that seek to develop their sugar industries. The article analyses the effects of EU sugar market reforms on three African countries — Nigeria, South Africa and Mozambique — and provides insights into the balancing of the EU sugar policy’s intended effects against their adverse effects on European trade and development policy.
CRIS-Team Scopus Importer:2022-11-17

State aid and state aid control in the agricultural sector Staatliche Beihilfen und Beihilfenkontrolle im Agrarsektor - Paha, Johannes; Zwerenz, Anna Lena (Wirtschaftsdienst, 2013)
In 2010, EU member states granted worth yy10.3bn aid to their agricultural sector. Given the requirement to revise the guidelines for state aid in the agricultural sector by the end of 2013, this article presents the legal rules and facts of this topic from an economic point of view. It is shown that economic methods which have been increasingly used in state aid control for non-agricultural sectors since 2005 can also be used for the analysis of state aid in the agricultural sector. Additional research is required to further develop these methods and establish the benefi ts of their application. © 2013 ZBW and Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-11-17

Sustainability Agreements and First Mover Disadvantages - Paha, Johannes (Journal of Competition Law and Economics, 2023)
This article presents a model where the managers of two firms decide about adopting a sustainable production technology (or product). It demonstrates under what conditions a firm experiences a first mover disadvantage from going green, which may potentially be overcome by a sustainability agreement serving as a device for equilibrium selection in a coordination game with multiple equilibria. If the technology adoption game is, however, a prisoner's dilemma, the sustainability agreement must be structured like a hardcore cartel.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Anticompetitive agreement; Climate; competition policy; Coordination game; First mover disadvantage; Sustainability

The Value of Collusion with Endogenous Capacity and Demand Uncertainty - Paha, Johannes (Journal of Industrial Economics, 2017)
Collusion has often been alleged in industries where long-lived capacity investments are important. This article develops a computational duopoly model with capacity investments, demand shocks and either competitive or collusive pricing. It shows that allowing for endogenous capacity investments can sometimes make collusion less valuable than competition and that it can change the normal relationships between the profitability of collusion and both the discount rate and industry-wide demand shocks.
CRIS-Team Scopus Importer:2022-11-17

Using accounting data in cartel damage calculations: Blessing or menace? - Paha, Johannes (European Journal of Law and Economics, 2012)
Standard methods for calculating cartel-damage rely on data of prices charged and quantity sold. Such data may not easily be available. In this paper, it is shown that accounting data can be used for computing a lower bound for cartel-damage. Previous literature indicates that economic profits can hardly be inferred from accounting data. Therefore, it is shown under which econometrically testable assumptions on accounting costs a meaningful lower bound for cartel-damage can consistently be estimated when using accounting data. However, the aggregation-level and the publication-frequency of accounting data pose a challenge to the estimation of cartel-damage. A further challenge is to appropriately reflect the strength respectively effectiveness of the collusive agreement in the specification of any such estimation. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Accounting data; Cartel damages; Cartel prosecution; Collusion